PUSAT EKONOMI KREATIF SENEN: MENGHIDUPKAN KAWASAN PERDAGANGAN DI SENEN - Jovan Kendrix; Agnatasya Listianti Mustaram (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
Senen is an area known as the center of economy, trade, and a bustling youth gathering place in its time. But after the monetary crisis that caused riots, many traders who lived in Senen area decided to move. The degradation that occurred caused the Senen area, which was previously called as the Senen Triangle and was the center of trade. But now less than optimal and only relied on a few places that were busy with buying and selling activities. With the narrative architecture method, the Senen area which was previously degraded due to the monetary crisis can again become a trading center, which can improve the economy of the Senen community. One way is by utilizing UMKM around the Senen area to be used as an adaptive creative economy in order to adapt to modern era. Senen Creative Economy Center is expected to be a solution to improve the economy, especially the creative economy such as UMKM. In addition to improving the economy for the surrounding community, the Senen Creative Economy Center is also expected to be a gateway to introduce a glimpse of the Senen area. With the Creative Economy Center, this area is expected to adapt to the times and can restore and restore the Senen area as an economic place and gathering place. Keywords:  Creative Economy; Degradation; Urban Acupuncture Abstrak Senen adalah kawasan yang lekat dengan pusat perekonomian, perdagangan, dan juga tempat berkumpul anak muda yang ramai pada masanya. Namun setelah terjadinya krisis moneter yang menyebabkan adanya kerusuhan menyebabkan banyak pedagang yang tinggal di daerah Senen memutuskan untuk pindah. Degradasi yang terjadi menyebabkan kawasan Senen yang sebelumnya dijadikan sebagai Segitiga Senen dan merupakan pusat perdagangan menjadi kurang maksimal dan hanya bertumpu dibeberapa tempat saja yang ramai dengan kegiatan jual beli. Dengan metode narrative architecture, Kawasan Senen yang sebelumnya mengalami degradasi akibat krisis moneter dapat kembali menjadi pusat perdagangan, yang dapat meningkatkan perkonomian masyarakat Senen. Salah satu caranya dengan memanfaatkan UMKM yang ada disekitar kawasan Senen untuk dijadikan sebagai ekonomi kreatif yang adaptif agar dapat beradaptasi dengan era modern sekarang ini. Tujuan dari Pusat Ekonomi Kreatif Senen yaitu dapat menjadi solusi untuk meningkatkan perekonomian terutama ekonomi kreatif seperti UMKM. Selain untuk meningkatkan ekonomi untuk masyarakat sekitar Pusat Ekonomi Kreatif Senen juga diharapkan dapat menjadi gerbang untuk memperkenalkan sekilas kawasan Senen. Dengan adanya Pusat Ekonomi Kreatif, kawasan ini diharapkan dapat beradaptasi dengan zaman dan dapat mengembalikan serta memulihkan kawasan Senen sebagai tempat ekonomi dan tempat berkumpul.